Determination of Some Characters of Natural Orchardgrass Plants Collected from Different Places of Ondokuz Mayis University Campus Area II: Content of Some Nutritional Components† - MUT, HANIFE; AYAN, ILKNUR (Asian Journal of Chemistry, 2010)
This study was conducted to determine some nutritional elements of natural orchardgrass plant (Dactylis glomerata ssp. glomerata) which were collected from different places of Ondokuz Mayis University Kurupelit Campus in 2002- 2003 years. Average crude protein content was found as 6.38 % in 2002, whilst it was determined as 7.34 % in 2003. Average crude ash content studied in orchardgrass plants were 10.11 and 10.15 % in both 2 years, respectively. Ca, Mg, K contents in orchardgrass plants which were grown naturally were determined between 0.27-0.50 %, 0.10-0.14 %, 1.46-2.01 %, respectively. It was determined that Fe, Zn, Cu and Mn contents of collected samples were exceeded average values and adequate.